The Influence of Leadership Style on Employee Performance at PT Astra International ISUZU, Tbk Medan Branch - Damanik, Evo Marisi Tumpal; Simarmata , Bangettua; Sitanggang , Mery Suliyanti H.; Simbolon , Riani (Universitas Dehasen Bengkulu, 2025)
This research is entitled The Influence of Leadership Style on Employee Performance at PT Astra International Tbk - Isuzu Medan Branch. This study aims to determine the influence of leadership style on employee performance at PT Astra International Tbk – Isuzu Medan Branch The type of research data used is quantitative data. With data sources using primary and secondary data. The data collection technique used is a questionnaire with the number of samples in this study is 35 employees. The data analysis techniques used are Descriptive Statistical Analysis, namely validity tests, reliability tests, simple linear regression tests and hypothesis tests. Data testing using SPSS program tools. Based on the results of the validity test conducted by the author because R calculates > from the R value of the table, which is above 0.338. So that the questionnaire can be declared valid and can be used as research material. Based on the results of the regression analysis, the data shows the following equation: Y = 15.007 + 0.420. The results show that leadership style (X) has an influence of 0.420 on employee performance (Y). Based on the hypothesis, the partial test (t-test) shows that the leadership style variable (X) has a significant effect on employee performance where the t-value of the > calculation from the t-table is 3.469 > 2.036 with a significant level of 0.001 < 0.05 on employee performance (Y) so that the hypothesis that there is an influence of leadership style on employee performance at PT Astra International Tbk – Isuzu Medan Branch is partially accepted and proven to be true.